The granting of improper legitimity to the civil actor, to intervene in the punitive claim of the criminal process - Rivera Fernández, Ryder Hans (2023)
Our criminal procedure system confers the possibility of requesting two claims from the court when a criminal act has been committed. The first of these is the criminal claim, whose owner is the Public Ministry; The second claim is civil compensation, which is claimed by the aggrieved party constituted as a civil actor. However, the present research work manages to demonstrate that in the casuistry the criminal judges grant undue legitimacy to the civil actor to claim a criminal claim that it is not their responsibility to defend, even arrogating ownership of the criminal action of the Public Ministry. It is possible to prove that the civil actor has subordinated his claim for compensation to the prior conviction of a crime, contrary to what is stipulated in the Criminal Procedure Code of 2004. It is also shown that criminal judges agree to various requirements of the civil actor regarding the conduct punitive of the investigated many times in contrast to the decision made by the Public Ministry. It is concluded that the de facto legitimacy improperly granted to the civil actor ends up subjecting the investigated to a double criminal prosecution, one from the Public Ministry, and another, exclusive to the civil actor.